2008
DOI: 10.1038/modpathol.3801018
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma: guiding EGFR-targeted therapy and beyond

Abstract: Somatic mutations in certain tyrosine kinases have emerged as central 'drivers' of specific cancers and these mutant proteins are proving to be excellent substrates for targeted therapies. This is the case for mutant EGFRdependent lung adenocarcinomas, where EGFR mutation testing is already being used to help guide treatment decisions. Here, we provide an overview of the biology of EGFR-targeted therapies and the clinical experience to date, the positive and negative predictors of response, pathologic correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
228
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(240 citation statements)
references
References 72 publications
5
228
0
5
Order By: Relevance
“…Large cell carcinoma, appears to harbor EGFR mutations very rarely. 27,138,139 In one study, only one L858R mutation was found in 60 large cell carcinomas of lung. 139 In the study of Marchetti et al, 27 EGFR mutations were identified in 39 (10%) of 375 adenocarcinomas, but no EGFR mutations were found in 454 squamous carcinomas and 31 large cell carcinomas.…”
Section: Other Alterations That Affect the Egfr Tki Responsementioning
confidence: 98%
See 1 more Smart Citation
“…Large cell carcinoma, appears to harbor EGFR mutations very rarely. 27,138,139 In one study, only one L858R mutation was found in 60 large cell carcinomas of lung. 139 In the study of Marchetti et al, 27 EGFR mutations were identified in 39 (10%) of 375 adenocarcinomas, but no EGFR mutations were found in 454 squamous carcinomas and 31 large cell carcinomas.…”
Section: Other Alterations That Affect the Egfr Tki Responsementioning
confidence: 98%
“…215 As BRAF mutations are mutually exclusive to EGFR and KRAS mutations, it is likely to be associated with lack of response to EGFR TKIs. 138 …”
Section: Braf Mutationmentioning
confidence: 99%
“…14 Likewise, the detection of an EGFR exon 19 or 21 mutation in nonesmall cell lung cancer is correlated with sensitivity to EGFR tyrosine kinase inhibitors, including gefitinib and erlotinib. 15 Concomitant NGS analysis of a select set of genes with relevance across a broad scope of cancers increases the likelihood of detecting rare but clinically actionable variants (such as KIT mutations, which are present in <10% of thymic carcinomas 16 ), is an aid in selecting therapeutics for tumors harboring multiple genetic changes (such as combination therapies used for synergistic suppression), and allows for a tailored treatment regimen and more personalized patient care. 17 Unlike single-gene tests, applied chiefly to cancer types commonly harboring mutations in one gene, the use of NGS-based testing of multiple oncology targets also allows for detection of rare and at times unexpected genetic variation.…”
mentioning
confidence: 99%
“…KRAS-Mutationen wurden als eine der ersten Onkogenalterationen beim Lungenkarzinom erstmals 1987 beschrieben [11]. Bei nichtkleinzelligen Karzinomen kommen sie in 10-15% vor, am häufigsten beim Adenokarzinom mit 20-30% [28].…”
Section: Globale Genexpression Und Epigenetische Markerunclassified
“…Diese Mutationen sind jeweils gegenseitig exklusiv, d. h. es ist lediglich eines dieser vier Onkogene mutiert, was auch tumorbiologisch Sinn macht, da eine Mutation ausreicht, um den Signalweg zu aktivieren. Des Weiteren wurden Punktmutationen im PIK3CA beschrieben, die zusammen mit anderen Alterationen des EGFR-KRAS-Signalwegs vorkommen können [11].…”
Section: Globale Genexpression Und Epigenetische Markerunclassified